Lithium fine-tunes biodegradation of Zn-based implant to promote osseointegration through immunomodulation - Danni Shen; Wei Qiao; Xiaoxue Xu; Shery L.Y. Chang; Thomas E. Lockwood; Wenting Li; Parkarsh Kumar; Jie Shen; Jun Wu; Feihong Liu; Kelvin W.K. Yeung; Yufeng Zheng (Bioactive Materials)
The intricate degradation dynamics exhibited by biodegradable alloys significantly influence host responses during the implantation process, posing challenges in achieving stable osseointegration. It is thus critical to tailor the biodegradation profiles of these implants to establish a conductive tissue microenvironment for bone tissue regeneration. In this study, we demonstrate that Zn-Li alloy forms a layer of Li-containing degradation products at the bone-implant interface to accommodate the bone regeneration process. During the early inflammatory phase, the controlled release of lithium ions (Li+) and zinc ions (Zn2+) from the alloy induces chemokine (C-C motif) ligand 5 (CCL5) production from macrophages, which promotes the recruitment and differentiation of osteoblastic lineage cells. As a protective bone-implant interface is formed subsequently, the active Zn2+ release from Zn-Li alloy is suppressed while Li+ continues to exhibit anti-inflammatory effects and inhibit osteoclastogenesis. Therefore, the presence of Li in Zn-based alloy prevents the prolonged inflammation and fibrous capsulation typically seen in pure Zn implants. Our findings offer valuable insights into the development of novel biodegradable implants aimed at achieving osseointegration through bioadaption.